Forty-Year Trends in Tooth Loss Among American Adults With and Without Diabetes Mellitus: An Age-Period-Cohort Analysis - Luo, Huabin (Prev Chronic Dis, 2015)
INTRODUCTION: This study aimed to assess the trends in tooth loss among adults with and without diabetes mellitus in the United States and racial/ethnic disparities in tooth loss patterns, and to evaluate trends in tooth loss by age, birth cohorts, and survey periods. METHODS: Data came from 9 waves of the National Health and Nutrition Examination Survey (NHANES) from 1971 through 2012. The trends in the estimated tooth loss in people with and without diabetes were assessed by age groups, survey periods, and birth cohorts. The analytical sample was 37,609 dentate (ie, with at least 1 permanent tooth) adults aged 25 years or older. We applied hierarchical age-period-cohort cross-classified random-effects models for the trend analysis. RESULTS: The estimated number of teeth lost among non-Hispanic blacks with diabetes increased more with age than that among non-Hispanic whites with diabetes (z = 4.05, P < .001) or Mexican Americans with diabetes (z = 4.38, P < .001). During 1971–2012, there was a significant decreasing trend in the number of teeth lost among non-Hispanic whites with diabetes (slope = −0.20, P < .001) and non-Hispanic blacks with diabetes (slope = −0.37, P < .001). However, adults with diabetes had about twice the tooth loss as did those without diabetes. CONCLUSION: Substantial differences in tooth loss between adults with and without diabetes and across racial/ethnic groups persisted over time. Appropriate dental care and tooth retention need to be further promoted among adults with diabetes.